Elektroniczny dokument medyczny jako innowacja technologiczna w nowoczesnej organizacji non profit - Rosak, Joanna; Borkowski, Stanisław (Electronic medical document - technological innovation in the modern non-profit company, 2006)
Non-profit companies are institutions operating for the public welfare, but not oriented to the profit. Cash balances of sick people can be the example, in which the commodity i.e. the subject of the market, is health or the other product of the immaterial character. Electronic medical document (ERM) is becoming necessary for the co-ordination of the patient care within the network of incorporated hospitals, the out-patient clinic, balances of sick people and private surgeries. A method of functioning the electronic medical document was presented in the article. It shows that this is the new, unique technology that is able to fundamentally change the quality of the system of medical services in Poland making the revolution in management with budgetary expenditure.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 269-275